2016
DOI: 10.4049/jimmunol.1502294
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Adenosine Deaminase on Induced Mouse Experimental Autoimmune Uveitis

Abstract: Adenosine is an important regulator of the immune response and adenosine deaminase (ADA) inhibits this regulatory effect by converting adenosine into functionally inactive molecules. Studies have shown that adenosine receptor (AR) agonists can be either anti- or pro-inflammatory. Clarification of the mechanisms that cause these opposing effects should provide a better guide for therapeutic intervention. In this study, we investigated the effect of ADA on the development of experimental autoimmune uveitis (EAU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Meanwhile, supernatants collected from activated and non-activated γδ T cells had a similarly enhancing effect ( Fig 4C ). We also tested the effect of γδ T cell supernatants after incubation with an adenosine-degrading enzyme ADA ( Fig 4D ) [ 31 33 ]. Interestingly, after ADA treatment the γδ T cell supernatant lost its enhancing effect ( Fig 4D , right panel).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, supernatants collected from activated and non-activated γδ T cells had a similarly enhancing effect ( Fig 4C ). We also tested the effect of γδ T cell supernatants after incubation with an adenosine-degrading enzyme ADA ( Fig 4D ) [ 31 33 ]. Interestingly, after ADA treatment the γδ T cell supernatant lost its enhancing effect ( Fig 4D , right panel).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies on the effect of extracellular adenosine on autoimmune responses [ 31 35 ] have shown that such molecules have a strong effect on this autoimmune response [ 31 , 33 36 ]. Given that adenosine is a metabolite of ATP and that dysfunction of P2X7R signaling impaired T-cell function and suppressed T-cell activation [ 5 , 17 , 37 ], we wished to determine the effect of extracellular ATP signaling on autoimmune uveitis and the effect of blocking ATP binding on Th1 and Th17 autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have established reliable assays for testing the effect of γδ T cells on autoimmune responses, in vitro and in vivo [ 3 , 4 , 32 35 ]. Testing of the adenosine effect used responder αβ T cells prepared from immunized TCR-δ -/- mice because the αβ T cell response to adenosine is strongly affected by <1% of γδ T cells [ 3 , 4 , 32 35 ]. T cell responses to the immunizing antigen were determined in the absence or presence of γδ T cells [ 3 , 4 , 32 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Testing of the adenosine effect used responder αβ T cells prepared from immunized TCR-δ -/- mice because the αβ T cell response to adenosine is strongly affected by <1% of γδ T cells [ 3 , 4 , 32 35 ]. T cell responses to the immunizing antigen were determined in the absence or presence of γδ T cells [ 3 , 4 , 32 35 ]. As expected, the addition of activated γδ T cells, but not of non-activated, γδ T cells, significantly enhanced the Th17 but did not enhance the Th1 response [ 5 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation